Pengaruh Promosi Dan Kualitas Pelayanan Terhadap Keputusan Pembelian Sepeda Motor Honda Pada PT Wahanaartha Ritelindo Cabang Ciputat - Sundapa, Melani; Mubarok, Ali (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The purpose of this study is to determine the Promotion and Service Quality on Purchasing Decisions at PT. Wahanaartha Ritelindo Ciputat Branch both partially and simultaneously. The method used is quantitative. The population in this study was 4,000 consumers with the sampling technique using random sampling and the sample obtained in this study amounted to 100 respondents. The results of this study that Promotion has a significant effect on Purchasing Decisions with a simple regression equation Y = 30,878 + 0.207X1. Hypothesis testing obtained a calculated t value> t table or (5.720> 1.978). Thus Ho1 is rejected and Ha1 is accepted meaning there is a significant influence of Promotion on Purchasing Decisions. Service Quality does not have a significant effect on Purchasing Decisions simple regression equation Y = 30,878 + 0.049X2. Hypothesis testing obtained a calculated t value> t table or (1.276 <1.978). Thus Ho2 is accepted and Ha2 is rejected meaning there is no significant influence of service quality on Purchasing Decisions. Promotion and Service Quality on Purchasing Decisions are generated using the multiple regression equation Y = 30,878 + 0.207X1 + 0.049X2. The hypothesis test obtained a calculated F value > F table or (17,439 > 2.670). Thus, Ho3 is rejected and Ha3 is accepted, meaning there is a significant simultaneous influence of Promotion and Service Quality on Purchasing Decisions